Sistem Informasi Prestasi Kerja Dan Pelayanan Umum Berbasis Web Pada Kantor Camat Toili Barat - I Ketut Putra Yasa; I Ketut Purwanto (Akademi Manajemen Informatika dan Komputer Luwuk Banggai, 2022)
The purpose of writing this final project is to design and build a Web-Based Work Performance and Public Service Performance Information System at the Toili Barat District Office using the HTML, CSS, PHP MySQL programming language, which aims to assist the West Tili District Government in the process of employee management and service general district. The research method used in this study is the descriptive method, and the data collection method is the observation method (direct observation), the interview method and the library method. As a result of the research, a web-based work performance and public service information system was created, which helps government activities in West Toili sub-district.